Implementation of EcoSufism-Based Learning in Creating Mental Balance of Santri in Pesantren - Masturin, Masturin; Nadhirin, Nadhirin (Program Studi Pendidikan Agama Islam, 2024)
This study aims to explore the implementation of ecosufism-based learning in pesantren and its role in shaping environmentally conscious students while achieving mental balance. This research was conducted at Al Mawaddah Islamic Boarding School in Kudus and Edi Mancoro Islamic Boarding School in Salatiga. Data were collected through observation, interviews, and documentation, and analyzed using descriptive thematic approach. The Al-Mawaddah Islamic Boarding School integrates the agricultural sector as a medium to cultivate students with spiritual, intellectual, leadership, and entrepreneurial excellence. Students uphold agricultural environments through eco-friendly practices as devotion to Allah. Meanwhile, the Edi Mancoro Islamic Boarding School incorporates ecosufism into the curriculum of its Islamic boarding school and affiliated educational institutions. Creating aesthetically pleasing surroundings while preserving a rural atmosphere reflects the institution's commitment to upholding eco-conscious and traditional practices. An Islamic-based environmental curriculum should address global challenges, promote environmental appreciation, and align with Islamic principles in education.